Biomechanics of Turtle Shells: How Whole Shells Fail in Compression1. Issue 2 (30th November 2012) - Magwene, Paul M.; Socha, John J.
Abstract Turtle shells are a form of armor that provides varying degrees of protection against predation. Although this function of the shell as armor is widely appreciated, the mechanical limits of protection and the modes of failure when subjected to breaking stresses have not been well explored. We studied the mechanical properties of whole shells and of isolated bony tissues and sutures in four species of turtles (Trachemys scripta, Malaclemys terrapin, Chrysemys picta, and Terrapene carolina) using a combination of structural and mechanical tests. Structural properties were evaluated by subjecting whole shells to compressive and point loads in order to quantify maximum load, work to failure, and relative shell deformations. The mechanical properties of bone and sutures from the plastral region of the shell were evaluated using three‐point bending experiments. Analysis of whole shell structural properties suggests that small shells undergo relatively greater deformations before failure than do large shells and similar amounts of energy are required to induce failure under both point and compressive loads. Location of failures occurred far more often at sulci than at sutures (representing the margins of the epidermal scutes and the underlying bones, respectively), suggesting that the small grooves in the bone created by the sulci introduce zones of weakness in the shell. Values for bending strength, ultimate bending strain, Young's modulus, and energy absorption, calculated from the three‐point bending data, indicate that sutures are relatively weaker than the surrounding bone, but are able to absorb similar amounts of energy due to higher ultimate strain values. J. Exp. Zool. 319A:86–98, 2012. © 2012 Wiley Periodicals, Inc.